A Comparative study of intrathecal hyperbaric Bupivacaine with or without Morphine for Post-Operative Analgesia in Hysterectomy - Basnet, Ujjwal (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The aim of the study is to compare the effect of addition of morphine with bupivacaine and bupivacaine alone in intrathecal anesthesia for the quality and the duration of analgesia in hysterectomy. Methods: Prospective randomized analytical study was conducted in patients undergoing hysterectomy under spinal anesthesia over period of one year. Patients were randomized into two groups: hyperbaric bupivacaine (15mg) only or hyperbaric Bupivacaine (15mg) plus Morphine (0.2mg). The mean duration for the request of first analgesia in post-operative period, mean visual analogue scale (VAS) score at the time of request of analgesia and common adverse effects were compared. Results: The post-operative analgesia was prolonged (260.32 Vs. 154.34 minutes) along with low VAS pain scale (5 vs. 7.5) in combination group but the respiratory depression was significantly high. Conclusions: The addition of morphine to hyperbaric bupivacaine prolongs the total duration of sensory analgesia, causes significantly greater frequencies of respiratory depression and causes no significant increase in other complications like hypotension, bradycardia, nausea and vomiting and pruritus, in comparison to patients receiving intrathecal hyperbaric bupivacaine only.